Examination Of The Relationship Between Religious Coping Styles And Mental Health During The Covid 19 Pandemic Period - Çetin, Çağla; Güzeloğlu, Tuğşat (Fırat University, 2022)
From the past to the present, it is an undeniable fact that there are many psychological problems in human life because of variety of stressors. There are many methods and ways of coping to face this reality and overcome the obstacles. Recently, pandemic is a huge topic which people have to be struggled. It is possible to say that preventing individuals from leaving the house by social isolation during the pandemic period causes depressive states by triggering feelings of loneliness, and it is possible to say that the feelings of being blocked by deprivation of freedom brings along many psychological problems. In this period, anxiety and uncertainty of pandemic that eliminate the functionality of the person have great psychological effects. Because of the reasons which were aligned above, coping mechanisms are most needed to get over stressful effects of pandemic. The pandemic period is a difficult period in which many individual experience social, economic and especially psychological problems. During this period, people use various coping methods to eliminate their psychological problems. Especially, studies show that religious coping has an important role in coping with psychological problems. To start with explaining the variables in the present study, in its most basic sense, religious coping is explained with the tendency to cope with the difficulties that we encounter in life through religious values. Similarly, religious coping is a form of thought or behavior that helps individuals avoid stress and the negative emotions that it causes. Religious coping is defined as constantly changing cognitive and behavioral efforts to combat certain external and/or internal urges that exceed or strain one's resources. To continue with psychological disorders, in order to understand psychological disorders, first of all, we need to understand psychological health. Psychological health can be defined as emotional and psychological well-being of people.

Geçmişten günümüze kadar bakıldığında, insan hayatında stres ve buna bağlı olarak birçok psikolojik sıkıntının var olduğu inkâr edilemez bir gerçektir. Bununla birlikte bu gerçekle yüzleşmek ve sıkıntıları ortadan kaldırmak için birçok yöntem ve başa çıkma yolu vardır. Başa çıkma yöntemlerine en çok ihtiyaç duyulduğu dönemlerden biri de pandemi dönemidir. Bu dönemde insanlar psikolojik sorunlarını ortadan kaldırmak için çeşitli baş etme yöntemleri kullanmaktadır. Yapılan çalışmalar dini başa çıkmanın psikolojik sıkıntılarla baş etmede önemli bir konuma sahip olduğunu göstermektedir. Bu yüzden çalışma pandemi döneminde kişilerin içinde bulunduğu ruhsal sıkıntılarla baş etmede dini başa çıkma tutumlarının etkisini incelemektedir. İncelemeyi gerçekleştirmek için çalışmada nicel araştırma yöntemleri ile “Dini Başa Çıkma Ölçeği” ve “Belirti Tarama Testi (SCL-90)” kullanılmıştır. Ölçekler, Bursa’da ikamet eden 165 katılımcıya uygulanmıştır. Örneklem, ulaşılabilirlik-elverişlilik ilkesine göre kolay örnekleme ve kartopu yöntemi kullanılarak belirlenmiştir. Sonuç olarak çalışmada elde edilen bulgular dikkate alındığında, pozitif ve negatif dini başa çıkmanın, ibadet sıklığı ile Belirti Tarama Testi arasında oluşturulan modelde anlamlı bir ilişki bulunmuştur. Dolayısıyla pandemi öneminde ibadet sıklığı, negatif ve pozitif dini başa çıkmanın ruhsal bozuklukların ortaya çıkışında ve engellenmesinde rolü olduğu sonucuna varılmıştır.
Covid 19 Pandemi Döneminde Dini Başa Çıkma Tarzları İle Ruh Sağlığı Arasındaki İlişkinin İncelenmesi
Keywords: Religious Studies; Din Araştırmaları